Notch3 Modulates Cardiac Fibroblast Proliferation, Apoptosis, and Fibroblast to Myofibroblast Transition via Negative Regulation of the RhoA/ROCK/Hif1α Axis - Shi, Jianli; Xiao, Peilin; Liu, Xiaoli; Chen, Yunlin; Xu, Yanping; Fan, Jinqi; Yin, Yuehui (Frontiers in Physiology, 2020)
Cardiac fibrosis is a common pathophysiological process of heart failure development for multiple cardiovascular diseases. The abnormality of cardiac fibroblast(CF) function is the key event of cardiac fibrosis. Notch signaling pathway and Hif1α was reported to be involved in several pathogenic processes including cardiac fibrosis under hypoxia.The role of Hif1α in Notch3-regulated CF function under normoxia remain unclear. The present study was designed to determinethe effect of Notch3 on CF function and its relation with Hif1α. First, we demonstrated that Notch3 inhibited cell proliferation, prevented cardiac fibroblast to myofibroblast transition and promoted apoptosis in CFs.The knockdown of Notch3 had the exact opposite effect. Next, we found Notch3 regulated CF function by negative regulation of RhoA/ROCK/Hif1α signal pathway under normoxia. Finally, extending CF-based studies to rat MI-model, overexpression of Notch3 by the Ad-N3ICD injection alleviated the elevation of RhoA, ROCK1, ROCK2 and Hif1α in MI and further prevented MI induced cardiac fibrosis. Based on these results, we conclude that Notch3 is involved in CF proliferation, apoptosis, and fibroblast to myofibroblast transition by negative regulation of RhoA/ROCK/Hif1α axis independent of hypoxia. These findings are significant to further understand the pathogenesis of cardiac fibrosis and provide new ideas for future treatment.